PENGARUH WADAH DAN LAMA PENYIMPANAN TERHADAP KUALITAS HASIL PENYULINGAN GETAH PINUS DARI SUMATERA BARAT - Bambang Wiyono; Poedji Hastoeti; Evi Kusmiyati (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Oleoresin of pine (Pinus merkusii) is a Non Wood Forest Products commodity from West Sumatra. This oleoresin was obtained by tapping pine trees with square system followed by light burning to stimulate more oleoresin exudate to bleed. This research was carried out to assess the effect of storage time and kind of plastic laminated container for pine resin collected from the field with square tapped method, on rosin recovery rate and its physicochemical properties.Prior to distillation, the pine oleoresin was kept in two kinds of containers, i.e. plastic laminated steel and plastic laminated aluminium. The distillation of pine oleoresin kept in plastic laminated container produced about 5863 % of rosin and 2026 % of turpentine oil, respectively. Meanwhile, the distillation products of pine oleoresin previously kept in plastic laminated aluminium amounted to 5663 % of rosin recovery and 2227 % of turpentine. Analysis of variance of the experimental results indicated that container and storage time caused significant effect on ash content of rosin. The ash content of rosin from pine oleoresin after being kept in plastic laminated steel container was somewhat lower than that of the one being kept in plastic laminated steel container. The storage time of pine oleoresin up to 6 weeks in aluminium container could produce the rosin still comply with its prime quality and equivalent to WW (Water White) quality of rosin. Meanwhile, the storage time of pine oleoresin in steel container could last only for 4 weeks to meet the requirement to produce at such quality. The prolonged storage time of pine oleoresin caused the decrease in rosin quality. It is concluded that a plastic laminated container can be used to keep pine oleoresin up to 6 weeks, and still rendering a prime quality rosin based on the Indonesian National Standard.